The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1038/onc.2014.317
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional effect of CD200 on breast cancer development and metastasis, with ultimate outcome determined by tumor aggressiveness and a cancer-induced inflammatory response

Abstract: CD200 acts through its receptor (CD200R) to inhibit excessive inflammation. The role of CD200-CD200R1 interaction in tumor immunity is poorly understood. In this study, we examined the role of CD200-CD200R1 interaction in the progression and metastasis of highly aggressive 4THM murine-breast carcinoma using CD200 transgenic (CD200(tg)) and CD200R1 knock-out (CD200R1(-)(/-)) BALB/c mice. 4THM cells induce extensive visceral metastasis and neutrophil infiltration in affected tissues. CD200 overexpression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
52
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 52 publications
8
52
1
Order By: Relevance
“…However, the results from these studies are more mixed, and none of these studies used the more aggressive mouse melanoma model. Thus, the discrepancy of previously published results with this study suggests that the role of CD200 in tumor immunity may differ in different tumor types (41), and may be associated with the tumor aggressiveness and its ability to induce inflammation, as suggested by a recent study (42) using CD200R-deficient mice.…”
Section: Discussioncontrasting
confidence: 93%
“…However, the results from these studies are more mixed, and none of these studies used the more aggressive mouse melanoma model. Thus, the discrepancy of previously published results with this study suggests that the role of CD200 in tumor immunity may differ in different tumor types (41), and may be associated with the tumor aggressiveness and its ability to induce inflammation, as suggested by a recent study (42) using CD200R-deficient mice.…”
Section: Discussioncontrasting
confidence: 93%
“…Murine 4T1 cells were originally isolated from a spontaneous mammary tumour in the BALB/c strain and have been reported as metastatic and also exhibit the characteristics of human basal/triple-negative breast cancer (TNBC) subtype14. In contrast, the EMT6 and 67NR murine cell lines have been shown to be less invasive1516. We first verified the tumorigenic and metastatic ability of EMT6 and 4T1 tumours, when 50,000 cells from both lines were injected into the mammary fat pads of, they produced similarly sized tumours within 8 weeks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Genetically engineered mice that overexpressed CD200 showed that the metastatic growth of breast tumor cells increased (14). By contrast, highly aggressive, but similar, breast carcinoma cells had decreased metastatic growth in a CD200-overexpressed host (16). These two opposing effects may be explained by the bidirectional characteristic of CD200.…”
Section: Discussionmentioning
confidence: 79%
“…The role of CD200 in breast cancer progression and metastasis has been studied in animal breast carcinoma model, where CD200 overexpression resulted in increased lymph node metastasis (14). By contrast, CD200 expression by melanocytes resulted in decreased lung metastasis (15) and decreased metastatic growth of breast carcinoma cells (16). Thus far, sCD200 has not been studied on human breast carcinoma subjects.…”
Section: Introductionmentioning
confidence: 99%